Annual Report on Exchange Arrangements and Exchange Restrictions 1973. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1973)
This paper highlights the exchange rate for the pound sterling soon after it began to float, moved within a relatively narrow range in relation to other major currencies and unrest in the exchange markets moderated. In some countries, such as Australia and Spain, where outward capital movements were still subject to considerable restrictions, these were relaxed to various extents. In a number of primary producing as well as industrial countries, the control of inward capital movements was motivated not by their immediate balance of payments impact but by concern over the extent of foreign ownership of certain sectors of the economy. Contrary to expectations, the monetary unrest remained and capital movements increased. After moderating somewhat in the second half of 1972, late in the period gold prices started to rise again, and they reached new peaks in early 1973. Guatemala, Hong Kong, and Kuwait abolished exchange control. Germany, invoking Article 23 of the Foreign Trade and Payments Law, restricted additional types of capital transactions between residents and nonresidents in order to ward off capital inflows.